Pneumomediastinum and pneumoretroperitoneum after COVID-19: concealed intestinal perforation - Jiaying Shen; Xiaoyong Shen; Feimin Zhao; Jianping Yao (BMC Infectious Diseases, 2024)
Abstract Background With the prevalence of coronavirus disease 2019 (COVID-19), many severe cases have been discovered worldwide. Here, a case of concurrent pneumomediastinum, pneumoretroperitoneum, and intestinal perforation was reported. This case was the first report on COVID-19-induced related complications. Case presentation A 74-year-old female patient was hospitalized for COVID-19. Air leakage was unexpectedly found during imaging reexamination. Considering the unobvious subjective feeling of the patient, a conservative treatment was given at the early stage, and finally, sigmoid colon perforation was surgically confirmed. The family gave up the treatment at last, because the patient could not be taken off the ventilator. Coincidentally, the patient also had abnormal renal anatomical position. This situation led to an abnormal air leakage direction and the atypical manifestations of peritonitis. It was also one of the important reasons for the delayed diagnosis and treatment of the disease. Conclusions Clinicians should be vigilant for spontaneous gastrointestinal perforation in patients with COVID-19, particularly those undergoing treatment with glucocorticoids and tocilizumab. The case is shared to highlight this rare and fatal extrapulmonary manifestation of COVID-19 and further assist clinicians to raise their awareness and timely implement imaging investigation and multidisciplinary intervention so as to facilitate early discovery, diagnosis and treatment and reduce the mortality.